A new genus and species of Anacolini (Coleoptera, Cerambycidae, Prioninae) from Bolivia - Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2018)
Nocalusa prodigiosa, new genus and new species of Anacolini, is described from Bolivia. A key to genera of American Anacolini based only on females is provided.